Leukotrienes are not essential for the efficacy of a heterologous vaccine against Mycobacterium tuberculosis infection - Franco, L. H.; Paula, M. Oliveira e; Wowk, P. F.; Fonseca, D. M. da; Sérgio, C. A.; Fedatto, P. F.; Gembre, A. F.; Ramos, S. G.; Silva, C. L.; Medeiros, Alexandra Ivo de [UNESP]; Faccioli, L. H.; Bonato, V. L. D. (Associação Brasileira de Divulgação Científica (ABRADIC), 2010)
Leukotrienes are reported to be potent proinflammatory mediators that play a role in the development of several inflammatory diseases such as asthma, rheumatoid arthritis and periodontal disease. Leukotrienes have also been associated with protection against infectious diseases. However, the role of leukotrienes in Mycobacterium tuberculosis infection is not understood. To answer this question, we studied the role of leukotrienes in the protective immune response conferred by prime-boost heterologous immunization against tuberculosis. We immunized BALB/c mice (4-11/group) with subcutaneous BCG vaccine (1 x 10(5) M. bovis BCG) (prime) followed by intramuscular DNA-HSP65 vaccine (100 µg) (boost). During the 30 days following the challenge, the animals were treated by gavage daily with MK-886 (5 mg·kg-1·day-1) to inhibit leukotriene synthesis. We showed that MK-886-treated mice were more susceptible to M. tuberculosis infection by counting the number of M. tuberculosis colony-forming units in lungs. The histopathological analysis showed an impaired influx of leukocytes to the lungs of MK-886-treated mice after infection, confirming the involvement of leukotrienes in the protective immune response against experimental tuberculosis. However, prime-boost-immunized mice treated with MK-886 remained protected after challenge with M. tuberculosis, suggesting that leukotrienes are not required for the protective effect elicited by immunization. Protection against M. tuberculosis challenge achieved by prime-boost immunization in the absence of leukotrienes was accompanied by an increase in IL-17 production in the lungs of these animals, as measured by ELISA. Therefore, these data suggest that the production of IL-17 in MK-886-treated, immunized mice could contribute to the generation of a protective immune response after infection with M. tuberculosis.
Keywords: Tuberculosis; Prime-boost immunization; Leukotrienes